Techniques of crime scene investigation - Fisher, Barry A. J. (CRC Press, 2022)
"Since the first English-language edition of Techniques of Crime Scene Investigation was published in 1964, the book has continued to be a seminal work in the field of forensic science, serving as a foundational textbook and reference title for professionals. This Ninth Edition includes several new chapters and has been fully updated and organized to present the effective use of science and technology in support of justice. New coverage to this edition addresses the debunking of a few forensic science disciplines, long thought to have been based on sound science. The book provides students, crime scene investigators, forensic scientists, and attorneys the proper ways to examine crime scenes and collect a wide variety of physical evidence that may be encountered. While it is not possible to cover every imaginable situation, this book is a comprehensive guide that details and promotes best practices and recommendations. In today's challenging environment, it is essential that law enforcement personnel thoroughly understand and meticulously comply with the forensic evidence procedures that apply to their function in the investigation process. Criminal investigations remain as complex as ever and require professionals from many disciplines to work cooperatively toward the fair and impartial delivery of justice. Practitioners and students alike need to be aware of the increased scrutiny that they will face in the judicial system. Judges are taking a more involved role than ever before as far as the evidence and testimony that they allow into their courtrooms. No longer will substandard forensic science or crime scene investigation be acceptable. Science and technology applied to CSI solves crimes and saves lives. Investigators, prosecutors, and defense attorneys must be able to use forensic tools and resources to their fullest potential and Techniques of Crime Scene Investigation serves as an invaluable resource to further this cause"--